Post a New Question

calculus

posted by on .

use the rule that says
limit of (e^h - 1)/h = 1 as h approaches 0
to show that the limit of [ln(x+h) -lnx]/h as h approaches 0 = 1/x, where x>0

  • calculus - ,

    ln(x+h)-lnx = ln[1 + (h/x)=
    -> h/x for x ->0

    Divide that by h and you get 1/x. The limit as x->0 is infinity

    I don't see how to use
    limit of (e^h - 1)/h = 1 as h approaches 0 to solve this
    e^h -1 -> h + h^2/2! + ... as h-> 0

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question